Infections in children with simple obesity: The relation to phagocytic function and serum leptin - Nadin N. Toaima; Rasha H. El-Owaidy; Dina L. Zaki; Lerine B. Eldin (Elsevier, 2019)
Introduction: There is a possible association between obesity and infections. We sought to investigate phagocytic functions in obese children and their relation to serum leptin levels. Methods: A cross sectional, controlled study was conducted, comprising 40 cases with simple visceral-type obesity. Subjects were evaluated for percentage of caloric intake, frequency and type of infections, body mass index (BMI) z score, in addition to complete blood counting, serum leptin assay (ELISA) and Dihydrorhodamine (DHR) flowcytometry. Results: Cases were 21 males (52.5%) and 19 females (47.5%) with mean age 7.14 years ± 2.73 SD with median duration of obesity 4.2 years (IQR: 2-6). Cases had higher frequency of infections compared with controls (p < 0.001). Serum leptin was significantly higher among cases (t = −12.391, p < 0.001), while DHR results were comparable in the studied groups (p = 0.067). Among cases, absolute lymphocytic count (ALC) correlated negatively with percentage of total caloric intake (p = 0.045). Leptin levels correlated positively with frequency of infections (p = 0.019) but negatively with ALC (p = 0.043). DHR results showed weak negative correlations with serum leptin (p = 0.177) and with BMI Z score (p = 0.109). Conclusion: Obese children are posed at increased risk of infections and have higher serum leptin levels with possible negative effects of leptin on phagocytic functions. Keywords: Obesity, Phagocytic function, Leptin, Infections, Calories